Book numbers : Indian and cutter - Satija, M. P. (New Delhi : Viva books, 2008)
This manual of book numbers explains the working mechanism of book numbers in all their intricacies. It illustrates the versatility of book numbering systems designed by Asa D. Dickinson, Sayyed Bashiruddin, S. R. Ranganathan, the National Library of India and Charles Ammi Cutter. Systems by Dickinson and Bashiruddin are now somewhat obscured by time. Here they are again brought to light. Dickinson method is a simplification of Cutter table made to suit Indian libraries at that time. Professor Bashiruddin devised author marks for books in Indian languages, including Urdu. His Hindi table has been described in detail with numerous newly devised examples of representative Hindi authors. His original table has been enormously expanded. Both these systems are for small libraries.
Includes index.
Keywords: Shelflisting -- India; Shelflisting